THE FAILURE OF CERTIFICATION PROGRAM TO UNIFY INDONESIAN TEACHERS’ PERCEPTION ON TEACHER PROFESSIONALISM: THE CASE OF BENGKULU JUNIOR AND SENIOR HIGH-SCHOOL TEACHERS - Arsyad, Safnil; Imrannudin, Imrannudin (TRIADIK, 2016)
Abstract: Teacher professionalism has become a very important topic for teachers in Indonesia including in Bengkulu since all teachers have been and will be certificated to be competent and professional teachers; however, they may still have various different perception on the topic. The purpose of this study is to know the perception of certificated teachers on professional teachers and how they should behave in and outside the school. The data of this study were obtained through a set of questionnaire distributed to 80 already certificated teachers. The results show that the majority of teachers still have different opinion on professional teachers and how they should behave in and outside the school. This implies that the certification intensive program is not effective enough to unify the teacher?s view on teacher?s professionalism. It is suggested that although they have been certificated, teachers must be introduced to characteristics of professional teachers and how to be professional teachers.